2010
DOI: 10.1002/etc.12
|View full text |Cite
|
Sign up to set email alerts
|

Potato (Solanum tuberosum) greenhouse tuber production as an assay for asexual reproduction effects from herbicides

Abstract: The present study determined whether young potato plants can be used as an assay to indicate potential effects of pesticides on asexual reproduction. Solanum tuberosum (Russet Burbank) plants were grown from seed pieces in a mineral soil in pots under greenhouse conditions. Plants were treated with herbicides (cloransulam, dicamba, glyphosate, imazapyr, primsulfuron, sulfometuron, or tribenuron) at simulated drift levels [ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The importance of measuring tuber production and not just vegetative shoot growth as an indicator of risk from low levels of herbicides was highlighted by the response of the young potato plants to sulfometuron. There was a much greater effect on tuber yield than on vegetative growth, measured especially as shoot dry weight (Olszyk et al, 2010). In this study, the results indicated that the sulfometuron had an influence on the source-sink relation of the potato plant and this caused the partition process to be unbalanced resulting in an accumulation of photosynthates in the plant aerial part.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The importance of measuring tuber production and not just vegetative shoot growth as an indicator of risk from low levels of herbicides was highlighted by the response of the young potato plants to sulfometuron. There was a much greater effect on tuber yield than on vegetative growth, measured especially as shoot dry weight (Olszyk et al, 2010). In this study, the results indicated that the sulfometuron had an influence on the source-sink relation of the potato plant and this caused the partition process to be unbalanced resulting in an accumulation of photosynthates in the plant aerial part.…”
Section: Discussionmentioning
confidence: 62%
“…In another study, soil residues of sulfometuron larger than 240 parts per trillion caused distorted tubers with cracks and folds (Hutchinson et al, 2007). Olszyk et al (2010) also observed that treatments with low levels of sulfometuron caused large reductions in tuber fresh weight. The effect on tuber fresh weight was due to reduced tuber size, insofar as it did not affect the number of tubers.…”
Section: Discussionmentioning
confidence: 88%
“…Al-Khatib and Tamhana [24] found reproductive losses with pea plants exposed to low levels of chlorsulfuron or metsulfuron but with more severe vegetative visible injury than noted by Fletcher et al [15]. Olszyk et al [22] did not find any consistent pattern in herbicide sensitivity at various stages of pea plant development, but confirmed that pea plants can have reduced seed yield with sulfonylurea herbicides.…”
Section: Toxicity Changes Based On Plant Developmentmentioning
confidence: 74%
“…Regardless of the environment in which we have grown potatoes, peas, and soybeans (large pots inside and out in the present study, small pots [22], or in the field [20]), the EC25s have generally been within a single order of magnitude for a particular species, herbicide, and response. Riemens et al [23] found differences based on herbicide used, with greenhousegrown plants being more sensitive to glufosinate ammonium, while field-grown plants were more sensitive to tepraloxydim.…”
Section: Location Effects On Ec25mentioning
confidence: 95%
See 1 more Smart Citation